Structural and magnetic properties of indium–gadolinium oxide as a function of temperature. Issue 9 (12th May 2015) - Qadri, S. B.; Wu, D. H.; Bussman, K.; Qadri, S. N.
<x xml:space="preserve">Abstract</x> The addition of In2O3 to Gd2O3 results in the formation of solid solutions having the high pressure monoclinic and hexagonal phases of gadolinium oxide. The thermal stability and their thermal expansion coefficients were investigated up to 1000 °C using in situ X‐ray diffraction. No phase transitions were observed in these samples up to 1000 °C. Volume thermal expansion coefficients for the hexagonal and monoclinic phases of bulk Gd2−xInxO3 for x = 0.5 and 1.0 showed increasing trend in comparison to the end compound of In2O3. The inverse susceptibility measurements between 300 and 5 K showed the linear relationship with temperature consistent with the Curie–Weiss law. The Weis constants were small and negative, indicating a slight degree of anti‐ferromagnetic exchange between cations and consistent with the absence of magnetic order down to 5 K.